Pengenalan HIV/AIDS melalui Kosakata Bidang HIV/AIDS di SMP Muhammadiyah 1 Kota Bandung - Perla Yualita (ACADEMICS IN ACTION Journal of Community Empowerment, 2020)
The number of people with HIV/AIDS in the world is increasing. The introduction of HIV/AIDS in the early adolescent phase needs to be done with a language approach that is easy to be understood and remembered. One of them is the approach to vocabulary recognition in the field of HIV/AIDS. The purpose of this community service activity was to discover the application of HIV/AIDS introduction through HIV/AIDS vocabularies. The method used was pre-experimental one group pretest-posttest design which began with pre-test, the provision of HIV/AIDS vocabulary materials through power points and distribution of HIV/AIDS vocabulary sheets. This experiment was ended by doing post-test. The final results showed an increase in the average score of 26.71% with significancy 0,00<0,05.. Thus, the introduction of HIV/AIDS through HIV/AIDS vocabularies is an effective effort to facilitate the early introduction of HIV/AIDS on to students in their early adolescent to avoid the dangers of HIV/AIDS.